The effectiveness of aquatic plants as surrogates for wider biodiversity in standing fresh waters. (15th July 2019) - Law, Alan; Baker, Ambroise; Sayer, Carl; Foster, Garth; Gunn, Iain D. M.; Taylor, Philip; Pattison, Zarah; Blaikie, James; Willby, Nigel J.
Abstract: Freshwaters are among the most globally threatened habitats and their biodiversity is declining at an unparalleled rate. In an attempt to slow this decline, multiple approaches have been used to conserve, restore or enhance waterbodies. However, evaluating their effectiveness is time‐consuming and expensive. Identifying species or assemblages across a range of ecological conditions that can provide a surrogate for wider freshwater biodiversity is therefore of significant value for conservation management and planning. For lakes and ponds in three contrasting landscapes of Britain (lowland agricultural, eastern England; upland, north‐west England; urban, central Scotland) we examined the link between macrophyte species, macrophyte morpho‐group diversity (an indicator of structural diversity) and the richness of three widespread aquatic macroinvertebrate groups (molluscs, beetles, and odonates) using structural equation modelling. We hypothesised that increased macrophyte richness and, hence, increased vegetation structural complexity, would increase macroinvertebrate richness after accounting for local and landscape conditions. We found that macrophyte richness, via macrophyte morpho‐group diversity, was an effective surrogate for mollusc, beetle, and odonate richness in ponds after accounting for variation caused by physical variables, water chemistry, and surrounding land use. However, only mollusc richness could be predicted by macrophyte morpho‐group diversity in lakes, with no significant predicted effect on beetles or odonates. Our results indicate that macrophyte morpho‐group diversity can be viewed as a suitable surrogate of macroinvertebrate biodiversity across diverse landscapes, particularly in ponds and to a lesser extent in lakes. This has important implications for the restoration, conservation, and creation of standing water habitats and for assessing their effectiveness in addressing the decline of global freshwater biodiversity. Management actions prioritising the development of species‐rich and structurally diverse macrophyte assemblages will be likely to benefit wider freshwater biodiversity.